Fibroblast growth factor 2 level and its relation to severity of illness in patients with schizophrenia: cross-sectional case–control study - Shamseldin, Noha; Baz, Heba; Mostafa, Nehal; Shahin, Mostafa (Middle East Current Psychiatry, 2025)
Background Schizophrenia (SCZ) is a severe and devastating psychiatric disorder with a lifetime prevalence of roughly 1%. Pathophysiology is intricate and little comprehended; nonetheless, genetics have a substantial role in the risk of this condition, with heritability exceeding 0.8. Fibroblast growth factor 2 (FGF2) levels are altered in the serum of individuals with schizophrenia, and FGF2 is associated with human neurogenesis and cognitive functions. Methods This is comparative cross-sectional research. A sample of 40 SCZ individuals and 40 healthy subjects were involved in the research. The patient’s recruitment was from Kasr Al Ainy Psychiatry and Addiction Treatment Hospital, Cairo University while healthy controls were recruited from the workers in Cairo University and were matched with the patients for the sociodemographic data. A sample of blood was taken from both groups to measure the serum FGF2. Version 28 of the Statistical Package for the Social Sciences (SPSS) was applied to conduct the statistical analysis. Results Patients with schizophrenia had a significantly lower serum FGF2 level in comparison to healthy subjects ( p -value < 0.001). In SCZ individuals, a positive correlation between serum FGF2 and the severity of illness was found to be statistically significant ( p -value < 0.001). Conclusion Unmedicated patients with schizophrenia showed lower levels of FGF2 in contrast to healthy controls. The level of FGF2 positively correlated with severity of illness in these cases.